Different sieving methods for determining the physical characteristics in ground corn - Biazzi H.M.* (2022)
© 2022, Eduem - Editora da Universidade Estadual de Maringa. All rights reserved.We evaluated various sieving methods to estimate particle size (PS) and geometric standard deviation (GSD) of ground corn. The corn had been previously divided in six fractions and each one ground in a hammermill (1-, 2-, 3-, 4-, 5-or 12-mm sieves). The stacked sieving method, with prior drying at 105ºC without agitators was the reference. We evaluated eight sieving methods, distributed in a factorial design (2 x 2 x 2 x 6), consisting of the following treatments: i) with and without agitators (two 25-mm rubber spheres), ii) with and without previous drying, iii) with a nest of test sieves set in a stacked or reverse, and iv) employing six ground corn degrees, totaling 48 treatments (four replicates). There was a linear increase in PS estimation for methods without drying and stacking and quadratic increases for the others. Reverse, drying, and agitator methodologies gave better sieving of corn, and consequently gave the lowest PS and highest GSD. The results were more pronounced for high-intensity grinding (hammermill sieve with small apertures) in which the differences between the reference method with the drying and reverse methods were up to 210 µm. Reverse sieving combined with agitators allowed the greatest passage of corn particles through the test sieves and promoted better characterization of ground corn.